Being and well-being : health and the working bodies of Silicon Valley - English-Lueck, J. A. (June Anne), 1953- (Stanford University Press, 2010)
As the great American work-benefit experiment erodes, companies are increasingly asking people to take responsibility for managing their own health. This book explores this health culture, detailing the biomedical, countercultural, and immigrant-based beliefs and practices that shape ideas about working, care-giving, and more.